2012
DOI: 10.1007/s00404-012-2576-z
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of intracranial dynamics by transcranial Doppler sonography in perioperative period in paediatric hydrocephalus

Abstract: The results of our study showed the alteration of Doppler parameters of cerebral circulation in newborns with hydrocephalus before the drainage procedure. The successful drainage operation leads to the improvement of haemodynamic parameters of cerebral circulation. However, the statistical analysis showed the influence of some intracranial factors-the asymmetry of dilatation of lateral cerebral ventricles and periventricular haemorrhagic lesions on the Doppler parameters of cerebral circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…The results of the study [319] targeted at children with hydrocephalus confirmed that asymmetric dilatation of cerebral ventricles had significantly influenced values of basal RI-ACA before drainage procedure and compressive RI-ACA after it. Statistical analysis showed that values of basal RI-ACA after drainage procedure and compressive RI-ACA before drainage procedure was not influenced by asymmetric dilatation of cerebral ventricles.…”
Section: The Presence Of Bilateral Asymmetric Ventriculomegaly Characmentioning
confidence: 54%
See 3 more Smart Citations
“…The results of the study [319] targeted at children with hydrocephalus confirmed that asymmetric dilatation of cerebral ventricles had significantly influenced values of basal RI-ACA before drainage procedure and compressive RI-ACA after it. Statistical analysis showed that values of basal RI-ACA after drainage procedure and compressive RI-ACA before drainage procedure was not influenced by asymmetric dilatation of cerebral ventricles.…”
Section: The Presence Of Bilateral Asymmetric Ventriculomegaly Characmentioning
confidence: 54%
“…Therefore, the authors of the study assume that Doppler parameters of the cerebral arteries are influenced by combination of increased intracranial pressure and dilatation of cerebral ventricles. Additionally, the results of the study confirmed that not only progressive but also stable dilatation of cerebral ventricles with increased intracranial pressure has a negative effect on cerebral circulation [319]. On the contrary, in neonates with stable dilatation of cerebral ventricles, in which drainage procedure was not necessary, basal Doppler parameters of blood flow in ACA reached normal values [400].…”
Section: The Presence Of Bilateral Asymmetric Ventriculomegaly Characmentioning
confidence: 74%
See 2 more Smart Citations
“…month and 18 years, and these studies occurred in settings outside the pediatric intensive care unit (PICU) [1][2][3][4][5][6][7]. Thus, the main issue with either technique is that there are few data in the PICU population, and the clinical meaning of transcranial Doppler findings in this population remains unclear.…”
mentioning
confidence: 99%